PSYCHOLOGICAL IMPACT OF PERSONAL CHARACTERISTICS IN THE FORMATION OF PROFESSIONAL RESPONSIBILITY (International Educators Conference, 2025)
This article scientifically examines the psychological factors influencing the development of the psychological potential and professional responsibility of future psychologists. Furthermore, the article provides a theoretical analysis of psychological aspects such as the interdependence of psychological potential and responsibility, internal motivation, needs, decision-making processes, and stress management skills.